2002
DOI: 10.1097/01.asn.0000023681.13865.25
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+-Dependent Transporters in Cystine-Loaded Human Renal Cells

Abstract: Abstract. Cystinosis is the most common cause of the renal Fanconi syndrome in children, leading to severe electrolyte disturbances and growth failure. A defective lysosomal transporter, cystinosin, results in intralysosomal accumulation of cystine. Loading cells with cystine dimethyl ester (CDME) is the only available model for this disease. This model was used to present electrophysiologic studies on immortalized human kidney epithelial (IHKE-1) cells that had been derived from the proximal tubule with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In concordance with this idea, a recent study using the IHKE-1 cell line demonstrated that CDME had an acute effect on the basal membrane potential, possibly due to activated K ϩ conductance (16). In the present study, we investigated the effect of CDME loading on mitochondrial ATP-generating capacity, superoxide production, and viability of control fibroblasts compared with cystinotic fibroblasts accumulating cystine due to a known genetic defect of the CTNS gene.…”
mentioning
confidence: 61%
“…In concordance with this idea, a recent study using the IHKE-1 cell line demonstrated that CDME had an acute effect on the basal membrane potential, possibly due to activated K ϩ conductance (16). In the present study, we investigated the effect of CDME loading on mitochondrial ATP-generating capacity, superoxide production, and viability of control fibroblasts compared with cystinotic fibroblasts accumulating cystine due to a known genetic defect of the CTNS gene.…”
mentioning
confidence: 61%
“…This effect was distinct from those on Na ϩ -dependent alanine transporter, which was inhibited after at least 30 min of incubation with CDME. As the hyperpolarization induced by CDME could be blocked by Ba 2ϩ , the authors concluded that CDME activated a K ϩ conductance (34).…”
Section: Discussionmentioning
confidence: 99%
“…These two tissues are the first to be affected in nephropathic cystinosis (2), and it is feasible that the order of tissues involved in the disease reflects the intrinsic sensitivity of each to apoptosis. CDME is known to disrupt renal tubule cell function in animal models and cultured cells (31)(32)(33), and it could be that exposure to CDME alone alters the redox potential sufficiently to trigger the apoptotic response (Figures 5 and 6). CDME also causes inhibition of Na ϩ -dependent transporters (33).…”
Section: Discussionmentioning
confidence: 99%
“…CDME is known to disrupt renal tubule cell function in animal models and cultured cells (31)(32)(33), and it could be that exposure to CDME alone alters the redox potential sufficiently to trigger the apoptotic response (Figures 5 and 6). CDME also causes inhibition of Na ϩ -dependent transporters (33). Free cystine has been known to be nephrotoxic in experimental animals since 1925 (34); however, the mechanism remains to be determined.…”
Section: Discussionmentioning
confidence: 99%